Analysis of Inhibiting Factors for Resolving Election Disputes Within the Authority of the Election Supervisory Board (Bawaslu) - Erniyanti, Erniyanti (Open Access Indonesia Journal of Social Sciences, 2023)
The Election Supervisory Board (Bawaslu) has an important role in maintaining democracy in Indonesia, one of which is through resolving election disputes. This research aims to analyze the factors that hinder the resolution of election disputes within the authority of Bawaslu. The research method used is qualitative with a case study approach. Research data was obtained through in-depth interviews with key informants, namely Bawaslu members, academics and election law practitioners. The research results show that there are several factors that hinder the resolution of election disputes within Bawaslu's authority, namely: Time limitations: Election process disputes must be resolved quickly, so Bawaslu is often pressed for time; Limited human resources: Bawaslu lacks competent human resources in handling disputes, especially at the regional level; Budget limitations: Bawaslu's budget is often insufficient for dispute resolution needs, such as court and witness costs; Lack of coordination: Coordination between institutions regarding election dispute resolution still needs to be improved; Dispute complexity: Election disputes are often complex and involve many parties, so they require a lot of time and effort to resolve.